Examination of ADHD Symptom Severity, Depression Symptoms, and Alcohol-Related Negative Consequences in College Students with ADHD. Issue 2 (April 2023) - Kaiser, Ariela J. E.; Shippen, Nellie A.; Oddo, Lauren E.; Vasko, John M.; Chronis-Tuscano, Andrea; Meinzer, Michael C.
College students with ADHD are at elevated risk for problem drinking behaviors and depression symptoms relative to their peers without ADHD. However, mechanisms underlying these constructs are unclear. This cross-sectional study examines two models: (1) alcohol-related negative consequences account for the covariation between ADHD symptom severity and depression symptoms and (2) depression symptoms account for the covariation between ADHD symptom severity and alcohol-related negative consequences. The sample included 106 college student drinkers with ADHD ( M age = 19.86, SD = 1.4). Results indicated that depression symptoms partially accounted for the covariation between ADHD symptom severity and alcohol-related negative consequences. Additionally, alcohol-related negative consequences partially accounted for the covariation between ADHD symptom severity and depression symptoms. Future directions and clinical implications are discussed such as understanding the bidirectional nature of these relationships longitudinally, improving alcohol and depression-related outcomes, and developing transdiagnostic treatments to address these comorbidities among young adults with ADHD.